(untitled) (Global Media Journal - German Edition, 2011)
The Football World Cup tournament ranks amongst the largest international sports events, captivating vast live and television audiences. A key characteristic of football can be seen in its community-building function. Football provides opportunities for identification, strengthening local and national bonds. But does this also apply to the still vague category of Europe? Does the televised coverage of the Football World Cup hold the potential to foster a European identity? This paper employs a quantitative content analysis of the German and British live-commentaries of the 2010 World Cup matches between European and non-European teams. It analyzes and compares the description and evaluation of European and non-European participants. TV-commentaries have proven an ability to influence the audiences ́ perception of the match. It is therefore assumed that the commentaries contribute to a feeling of European identity and unity – if they make the European category salient. The analysis reveals some differences in the portrayal of European and non-European participants with the commentators paying more attention to participants from European countries. Whereas the evaluation of the European and non-European teams differs, the evaluation of the individual football players is well-balanced. In regard to the analyzed criteria, British and German commentaries tend to be very similar.